2015
DOI: 10.4204/eptcs.200.3
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of models for order-sorted first-order theories using linear algebra and constraint solving

Abstract: Recent developments in termination analysis for declarative programs emphasize the use of appropriate models for the logical theory representing the program at stake as a generic approach to prove termination of declarative programs. In this setting, Order-Sorted First-Order Logic provides a powerful framework to represent declarative programs. It also provides a target logic to obtain models for other logics via transformations. We investigate the automatic generation of numerical models for order-sorted firs… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(13 citation statements)
references
References 14 publications
0
13
0
Order By: Relevance
“…In [10] we have shown that convex domains [12] provide an appropriate basis to the automatic definition of algebras and structures that can be used in program analysis with order-sorted first-order specifications. In the following definition, vectors x, y ∈ R n are compared using the coordinate-wise extension of the ordering ≥ among numbers which, by abuse, we denote using ≥ as well:…”
Section: Interpreting Predicates Using Convex Domainsmentioning
confidence: 99%
See 4 more Smart Citations
“…In [10] we have shown that convex domains [12] provide an appropriate basis to the automatic definition of algebras and structures that can be used in program analysis with order-sorted first-order specifications. In the following definition, vectors x, y ∈ R n are compared using the coordinate-wise extension of the ordering ≥ among numbers which, by abuse, we denote using ≥ as well:…”
Section: Interpreting Predicates Using Convex Domainsmentioning
confidence: 99%
“…In [10] no procedure for the automatic generation of predicate interpretations was given. We solve this problem by providing (parametric) interpretations for predicate symbols P of any rank w ∈ S + .…”
Section: Interpreting Predicates Using Convex Domainsmentioning
confidence: 99%
See 3 more Smart Citations